Efeito do período de armazenamento e peso do ovo sobre a qualidade e desempenho do pinto de corte - Guimarães, Bruno Evangelista (2019)
The objective of this research was to study if the period of storage of fertile eggs and egg weight has influence on the quality of day-old chicks and on the performance of broiler chicks. The experiment took place at the Federal Technological University of Paraná, Dois Vizinhos. 200-day old female broiler chicks of the Ross [marca registrada] lineage were used in the experiment, distributed proportionally among the treatments, which were combinations of two egg storage periods of pre-incubation eggs with two different egg weights, being: 3-day storage period of light eggs, 9-day storage period of light eggs; 3-day storage period of heavy eggs; and 9-day storage period of heavy eggs. They were considered light eggs when the weight was less than or equal to 59 grams and heavy eggs when it was bigger than 59 grams. Body weight, chick length, finger length and leg length (tarso-metatarsus) + toes were determined for assessing the quality of the oneday-old chick, and tona score. Gait score, VAL and VAR, pododermatitis and performance were evaluated. The performance, VAL and VAR and pododermatitis data, were submitted to analysis of variance (ANOVA) using the statistical program SAS (2018) at 5% of significance, if significant, means were tested by the Bonferroni test at 5% probability. Gait Score data were analyzed using the PROC FREQ procedure of the SAS, by the Qui Square test. The results found in this research indicate that there was no significant effect of three- and nine-day storage time and egg weight on the performance of day-old broiler chicks. But, the incidence of locomotor problems was observed, according to the growth of the birds. Which leads to productive and economic losses.